Comparative Analysis of Volatility and Value at Risk Using the GARCH Method in Measuring Sukuk and Bonds in Publicly Listed Companies in Indonesia - Femei Purnamasari; Weny Rosilawati (LP2M IAIN Palopo, 2024)
This study aims to analyze the volatility and investment risks of sukuk and bonds in publicly listed companies in Indonesia using the GARCH method. The research data includes sukuk indices (ICSIX, IGSIX, ISIXC) and bonds collected from the Indonesia Bond Pricing Agency (IBPA) during the 2019-2020 period. The ARCH/GARCH model was employed to measure volatility, while Value at Risk (VaR) was utilized to estimate maximum risk. The findings indicate that ICSIX exhibits the lowest risk with a VaR value of 0.00124, whereas ISIXC demonstrates the highest risk at 0.006267, reflecting significant volatility. Moreover, the EGARCH (2,2) model is identified as the most suitable for ICSIX, while ARCH (1) is optimal for IGSIX. However, analysis on ISIXC is limited due to its failure to meet heteroskedasticity assumptions. This research contributes by providing insights for investors regarding risk management and investment decision-making in the Islamic capital market. Nonetheless, the study is constrained by the data used and does not incorporate external variables such as macroeconomic factors. Future research is suggested to expand the data scope and explore other volatility models, such as Stochastic Volatility, to provide more comprehensive insights into the dynamics of sukuk and bond investments.